Analisis Tren Penjualan serta Faktor yang Memengaruhi Penjualan Karet pada PT. XYZ - Huda, Muhammad Syamsul; Santoso, Siswanto Imam; Nurfadillah, Suryani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aimed to: 1) analyze the sales trend of rubber at PT XYZ; and 2) analyze the factors that influenced rubber sales at PT XYZ. The research was conducted from December 2024 to January 2025 at PT XYZ. The method used was a case study, considering that the rubber industry was facing challenges such as global market price fluctuations, climate change, and increasing competition. Analyzing sales trends and the influencing factors was important to formulate appropriate business strategies. The data used included rubber product prices, cost of goods sold, and marketing expenses. The data analysis methods employed were quantitative analysis, including trend analysis and multiple linear regression. The results showed that the variables of cost of goods sold and marketing expenses had a significant effect on the rubber sales volume, while the variable of product price did not have a significant effect. The forecasting result using the quadratic trend method indicated that the rubber sales volume for the next 18 months was estimated to reach 457,751.31 kg. The conclusion of this study highlighted the importance of cost control and marketing strategies in maintaining sales volume amid the challenges in the rubber industry.